Craniocervical Posture Improvement Using Twin Block: A Scoping Review - Hanifa, Mulia Ayu; Indriyanti, Ratna (Syntax Corporation Indonesia, 2025)
Functional appliances, such as twin block, effectively treat for skeletal class II malocclusion. The twin block exerts a significant influence on mandibular growth, that contributes to the improvement of craniocervical posture. This scoping review aims to systematically map and evaluate the current literature on the effects of twin block appliance treatment on craniocervical posture. A scoping review followed to PRISMA-ScR guidelines. A comprehensive research conducted in three online databases-Scopus, Pubmed, Springer Link- from 2014-2024. Article selection followed the PCC framework. Studies about the impact of twin block appliance on craniocervical posture were included. A total of 49 articles selected after eliminating duplicates, four articles met the inclusion criteria. The findings from these studies indicate the effect of twin block appliance usage on craniocervical posture. The twin block appliance not only impacts skeletal and dentoalveolar changes, but also craniocervical posture. Evidence suggest that mandibular advancement may induce postural adaptations by altering the craniofacial and cervical spine relationship.